(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2018)
In this paper the bioclimatic indices (heat waves, heat index and humidity index) for 1966–1990 and 1991–2016 periods were developed and evaluated in accordance with the methodology of WMO for the Yerevan City. We have calculuded that in the last two decades the number and duration of heat waves have sharply increased. In the estimation of the heat index during the period 1991–2016, 20 cases with very hot days were observed, since in the early 1966–1990 period such days were not observed. Moreover, the assessment of the humidity index has shown that the accidents with dangerous days for 1991–2016 period has sharply increased from 60 cases to 334.